1984
DOI: 10.3354/meps014185
|View full text |Cite
|
Sign up to set email alerts
|

Primary production of microphytobenthos in the Ems-Dollard Estuary

Abstract: From 1976 through 1978 primary production of microphytobenthos was measured at 6 stations on intertidal flats in the Ems-Dollard estuary using the 14C method. The purpose of the measurements was to estimate the annual primary production at different sites in the estuary and to investigate the factors that influence the rates of primary production. Therefore benthic chlorophyll a and a set of environmental factors were measured. Only primary production correlated sigruficantly with chlorophyll a concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
141
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(160 citation statements)
references
References 36 publications
17
141
1
1
Order By: Relevance
“…6) is within the range previously reported from the Wadden Sea (Colijn & van Buurt, 1975;van Es, 1982;Rasmussen et al, 1983;Colijn & de Jonge, 1984). According to these studies, the annual primary production cycle can be explained largely by seasonal changes in temperature and daylength.…”
Section: Microbenthic Primary Production and Respirationsupporting
confidence: 66%
See 1 more Smart Citation
“…6) is within the range previously reported from the Wadden Sea (Colijn & van Buurt, 1975;van Es, 1982;Rasmussen et al, 1983;Colijn & de Jonge, 1984). According to these studies, the annual primary production cycle can be explained largely by seasonal changes in temperature and daylength.…”
Section: Microbenthic Primary Production and Respirationsupporting
confidence: 66%
“…The positive relationship with GPP, though, infers that chlorophyll a concentration in surface sediment at the two subtidal stations (A and M) could be a co-factor for the control of benthic primary production, as also suggested for a variety of sediments in the Dutch Wadden Sea (Colijn & de Jonge, 1984).…”
Section: Microbenthic Primary Production and Respirationmentioning
confidence: 99%
“…Colijn & Dijkema, 1981;Sundba¨ck, 1984;de Jong & de Jonge, 1995;Hamels et al, 2001) was found in the Soltho¨rn tidal flat. The highest mean value in the present study was 198.9 mg chl a m À2 , which ranks in the middle to upper range for intertidal sediments (Colijn & de Jonge, 1984;MacIntyre et al, 1996). The significant variations of abundance and chl a concentration found in May 2008 and May 2009 are probably related to the difference in sediment surface temperature (difference between the two months: 11 C).…”
Section: à2mentioning
confidence: 74%
“…Amphora is a common benthic microalgae found in coastal benthic and pelagic environments (Welker et al 2002;Kasim and Mukai 2006;Facca and Sfriso 2007). Benthic microalgal communities are important primary producers in a wide variety of shallow coastal areas (Cadee and Hegeman 1974;Colijn and De Jonge 1984;Cahoon and Cooke 1992;Barranguet 1997;Nelson et al 1999). Up to 40% of the photosynthetically fixed carbon is lost by benthic and pelagic diatoms as an extracellular release (Fogg 1983;Smith and Underwood 1998;Taylor and Paterson 1998).…”
Section: Introductionmentioning
confidence: 99%